MANAGEMENT FISIOTERAPI PADA KASUS HEMIPARESE SINISTRA e.c STROKE NON HEMORAGIC: A CASE REPORT - Kartija, Dwi Rahmah; Dwi Rosella Komalasari; Muhamad Nasuka (Journal of Innovation Research and Knowledge, 2023)
Hemiparesis is a condition where there is weakness on one side of the body or the inability to move a limb on one side. Stroke patients who experience hemiparesis who do not get proper treatment can cause pain, decreased muscle strength, and activity daily living. Exercise therapy is one method that can be done. The purpose of this study was to determine the effectiveness of exercise therapy for the conditions faced by patients, namely pain, decreased muscle strength and activity daily living. This study uses a case report. Interventions in the form of active ROM exercises, strengthening exercises, bridging exercises and transfers and ambulation were carried out 4 times. The results of this study were that there was a decrease in pain as measured by NRS, an increase in muscle strength as measured by MMT and activity daily living as measured by the Barthel Index.